Workplace incivility and work engagement: The mediating role of job insecurity and the moderating role of self‐perceived employability. (28th May 2021) - Guo, Ju; Qiu, Yanjun; Gan, Yongtao
Abstract : Drawing upon the job demand–resource model and the theory of existence, relatedness, and growth needs, we established and checked a model that connects workplace incivility to employee work engagement (i.e., vigor, dedication, and absorption) through job insecurity. Furthermore, we propose and test self‐perceived employability as the boundary condition of this connection. The conclusions of two substudies with time‐delay design provided evidence to support theoretical models. Specifically, the conclusions of both studies show that workplace incivility has negative impacts on work engagement (i.e., vigor, dedication, and absorption) through job insecurity. The results of Study 2 show that self‐perceived employability not only weakens the negative influences of job insecurity on work engagement (i.e., vigor, dedication, and absorption) but also moderates the mediating roles of job insecurity in the relationships between workplace incivility and work engagement (i.e., vigor, dedication, and absorption). The theoretical and practical implications and limitations are discussed based on the conclusions of the two substudies.